Mine water as a multidimensional resource: A critical process engineering review of water-energy‑carbon nexus technologies, maturity assessment and scale-up challenges - Che Lulu; Li Bo; Yang Ya; Yang Yu; Luo Ye; Li Tao (Journal of Water Process Engineering, 2026)

Engineering Co-N4 active sites in heptazine-porphyrin organic polymer to boost non-radical singlet oxygen generation in peroxymonosulfate activation - Xiang Li; Yu Tian; Yalong Xu; Bo Liu; Shi Zhou; Wei Jiang; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Synergistic effects of lipid degradation and the Maillard reaction: Decoding the flavor formation of charcoal-grilled lamb skewers based on flavoromics, sensomics, metabolomics, and lipidomics - Che Shen; Xinyu Jiang; Jiajin Sun; Meiyi Li; Ran Wang; Yunhui Zhang; Jing Tian; Lizhang Wu; Xiongfeng He; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Lighting enhancing food preference: Dynamic sensory perception and electroencephalogram (EEG) exploration of the impact of lighting environment on meat perception and purchase intention - Wenxi Qi; Yi Zhang; Bo Wang; Che Shen; Dengyong Liu (International Journal of Gastronomy and Food Science, 2026)

Temporal modulation of acidification, volatile aroma profiles and sensory attributes during lactic acid bacteria fermentation of Berliner Weisse - Bo-Jun Liao; Huei-Rong Guo; Chun-Neng Huang; Chen-Che Hsieh (Food Bioscience, 2026)

A dual-stream LSTM–XGBoost framework for mine water inflow forecasting: a case study of the Longfeng coal mine - Wang Hao; Li Bo; Zeng Yi Fan; Liu Pu; Chen Wei; Wang Ze Hui; Che Lu Lu (Journal of Hydrology, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

Intramolecular internal electric field and activated n-π* electronic transition co-promoted photocatalysis activity of carbon nitride: Mechanism and toxicity evaluation - Yanbin Chen; Tianyu Zhou; Chunbo Liu; Bo Hu; Guojie Liu; Guangbo Che (Journal of Environmental Sciences, 2026)

Decoding the dynamic formation of bolus: A multimodal fusion and simulation framework for texture perception-regulated oral processing - Che Shen; Xinyu Jiang; Lizhang Wu; Zidong Chen; Zihao Li; Ran Wang; Wenxi Qi; Yi Zhang; Xinying Zhou; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Characteristics and identification methods of acoustic reflected waves from borehole-intersected fractures - Bo Yang; Xiao-hua Che; Teng Zhao; Wen-xiao Qiao; Jun-qiang Lu; Bai-yong Men (Applied Geophysics, 2026)

Joint inversion of hydraulic and thermal parameter fields using a CNN-based framework and transient hydraulic tomography - Che-Wei Liang; Jui-Pin Tsai; Zi-Yan Chou; Chia-Hao Chang; Bo-Tsen Wang (Journal of Hydrology, 2026)

Built-in electric field constructed by asymmetric electron cloud distribution for facilitating photocatalytic H2O2 production in covalent organic frameworks - Chuanxue You; Yue Zhou; Meiting Yang; Jingyang Li; Bo Hu; Yunchao Ma; Linlin Liu; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Data-Driven assessment of demand response potential of residential loads based on LSTM-WGCNA and Customer directrix load - Bo Peng; Baolin Cui; Xin Ma; Che Liu (Energy and Buildings, 2026)

A hybrid assembly mechanism employs nonreducing polyketide synthase-like logic for partially reduced polyketide formation - Xianyan Zhang; Chuanteng Ma; Ziguang Deng; Xingtao Ren; Kaijin Zhang; Wenxue Wang; Luning Zhou; Yongchun Zhu; Guojian Zhang; Qian Che; Tianjiao Zhu; Hongan Long; et al. (Marine Life Science & Technology, 2026)
Fungal iterative type I polyketide synthases (iPKSs) are commonly classified into nonreducing (NR-), partially reducing (PR-), and highly reducing (HR-) polyketide synthases based on their assembly mechanisms and domain structures. These iPKSs have been considered functionally and evolutionarily distinct, characterized by clear boundaries. However, emerging genomic analyses suggest that the diversity of iPKSs in fungi is far from fully understood. Here, we describe the discovery and characterization of PbPKS1 from a marine-derived fungus Penicillium brocae HDN12-143, which exhibits an atypical domain organization arranged as KR-KS-AT-PT-ACP 1 -ACP 2 -CMeT-TE. Heterologous expression of PbPKS1 resulted in the production of two monohydroxybenzoic acids and two pyrones. In vivo and in vitro characterizations demonstrated that PbPKS1 has the capability to synthesize Cα-methylated partially reducing polyketides, yet involved a NR-PKS-like assembly mechanism, featuring a product template (PT) domain for aldol cyclization and a C-terminal thioesterase (TE) domain for product release. Phylogenetic analysis suggests that PbPKS1 belongs to a non-canonical PR-PKS (nPR-PKS) family, which is a minor grouping across the fungal kingdom, and possibly evolved from an NR-PKS through gene recombination. The discovery of nPR-PKS not only expands the diversity of iPKSs but also provides new insights into the evolutionary development of fungal iPKSs.

Decoding aroma perception of grilled lamb skewers: an EEG-MambaFusionNet framework integrating TDS and GC-IMS - Che Shen; Wenxi Qi; Yi Zhang; Ran Wang; Qi Jin; Kezhou Cai; Bo Wang; Dengyong Liu (Food Chemistry, 2026)

Molecular identification and characterization of a ‘Candidatus phytoplasma australasiaticum’ -related strain associated with Scaevola taccada virescence disease in China - Hai-Yan Che; Mei-Jiao Hu; Hai-Bo Long; Da-Quan Luo; Shao-Shuai Yu (Physiological and Molecular Plant Pathology, 2026)

Highly isolated interlayer Co-N4 fixed by heptazine promotes peroxymonosulfate activation to selectively generate singlet oxygen - Xiang Li; Bo Liu; Shi Zhou; Chunbo Liu; Guangbo Che; Wei Jiang (Journal of Hazardous Materials, 2026)

NO heterogeneous reduction during oxy-fuel combustion of semi-coke: The role of high-temperature rapid gasification - Pengqian Wang; Chenxi Zhang; Xingpeng Li; Jiaojiao Zhang; Yi Liu; Yongbo Du; Chang’an Wang; Defu Che; Bo Bai (Fuel, 2026)

Hydrological connectivity associated with salinity mediates wetland vegetation pattern and productivity in estuary - Bo Pang; Chunguang Che; Changzhi Yang; Tian Xie; Baoshan Cui; Yeling Liu; Qing Wang; Yuming Lu; Yina Li; Fang Gao (Journal of Environmental Management, 2025)

Novel insight into the heavy metal immobilization by coal fly ash-based geopolymers using machine learning and density functional theory - Kaizhi Yang; Bo Yang; Kezhou Yan; Yining Su; Longyi Zhao; Jungang Tang; Yu Che; Yanxia Guo (Waste Management, 2025)

Propagation-invariant spatiotemporal vortices - Junyi Ye; Zhiyuan Che; Jiajun Wang; Yi Zhang; Bo Wang; Wenzhe Liu; Lei Shi; Jian Zi (Science Bulletin, 2025)

Bio-based low dielectric dynamic covalent crosslinked network: Multi-coupling modification at the ionic, atomic, and molecular levels - Guoming Yuan; Zhijun Liu; Yifei Wu; Hui Yang; Yanhan Tao; Bo Yang; Kun Wu; Jun Shi; Guangwen Che (Chemical Engineering Journal, 2025)

Glycosylation on breast cancer cell surface promotes the internalization and enhances therapeutic efficacy of cationic antimicrobial peptide L-K6 - Bo Wang; Yiwei Zhao; Qiuju Zhang; Jiaqi Zhao; Che Wang; Dejing Shang (Toxicology and Applied Pharmacology, 2025)

Environmental nano-particulates induced pre-implantation embryonic toxicity in pluripotent stem cell-derived blastoids - Gaojing Liu; Yayuan Li; Xiuyun Liu; Wei Wang; Xiao Wen; Yange Che; Qiu Tu; Bo Zhao (Environmental Pollution, 2025)

Carbon nitride featuring a robust built-in electric field with ultra-high photocatalytic activity - Yue Xu; Tianyu Zhou; Wei Jiang; Bo Hu; Chunbo Liu; Guangbo Che (Chemical Engineering Journal, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Nonlinear dynamics and vibration mechanisms in air scroll compressors: A study on orbiting and fixed scroll pair - Xiao-Liang Yang; Bin Peng; Ming-Lang Che; Jian-Fei Shi; Zhi-Xiang Liao; Yu-Bo Zhang (International Journal of Refrigeration, 2025)

Bimetallic ion crosslinked hydrogels sequentially releasing immunomodulatory factors and osteogenic factors to promote bone integration of 3D printed titanium alloy prostheses - Xiao Sheng; Zhenjia Che; Chuncheng Shen; Jingtao Wu; Chenhao Qiu; Chenjie Tan; Junjie Mao; Bo Li; Hang Yu; Jianyou Li; Wei Liu; Chen Li; et al. (Chemical Engineering Journal, 2025)

Insight into VOCs source profiles by machine learning: Role of commonalities in synergistic pollution controls - Shuwei Zhang; Song Gao; Bo Wang; Zhukai Ning; Lingning Meng; Ming Hu; Xiang Che; Zheng Jiao (Journal of Hazardous Materials, 2025)

Dual-pathway photosynthesis H2O2 realized by carbon nitride with strong built-in electric field and awakened n-π* electron transition: Based on theoretical calculation guidance - Yuhan Yan; Tianyu Zhou; Chunbo Liu; Bo Hu; Guangbo Che (Chemical Engineering Journal, 2025)

Tailoring C-defect O-doping and n-π* transition awakened porous ultra-thin carbon nitride for efficient peroxymonosulfate activation: Performances and mechanism insight - Meng Tai; Guangbo Che; Tianyu Zhou; Honghui Teng; Chunbo Liu; Bo Hu (Journal of Environmental Sciences, 2025)

Nitrogen-rich carbon nitride activated peroxymonosulfate for the efficient photodegradation of 2, 4-dichlorophenol: Performance and mechanism insight - Tianyu Zhou; Siyi Wang; Meng Tai; Juan Du; Dongshu Sun; Guangbo Che; Linlin Liu; Chunhong Ma; Bo Hu (Environmental Research, 2025)

Development and evaluation of an electrical impedance tomography (EIT) sensor for real-time monitoring of hemolysis dynamics - Piao Peng; Yue Fu; Bo Che; Xuan Li; Lei Liu; Jing Sun; Teng Luo; Linhong Deng (Analytica Chimica Acta, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

High-precision U-series dating of Panxian Dadong hominin site, Guizhou Province, southwestern China - Xiaochao Che; Fei Han; Xingsheng Zhang; Bo Cao; Ping Xiao; Guanjun Shen; Jianxin Zhao (Quaternary Science Reviews, 2025)

Ticks jump in a warmer world: Global distribution shifts of main pathogenic ticks are associated with future climate change - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Wenwen Chen; Lianjin Liu; Xiaofang Zhou; Chong Chen; Xian Li; Yiyang Su; Lingyu Che; Guishuang Li (Journal of Environmental Management, 2025)

Environmental acidification drives inter-organ energy mobilization to enhance reproductive performance in medaka (Oryzias latipes) - Hsin-Ju Chuang; Ling Chiu; Bo-Jun Liao; Chun-Yung Chang; Guan-Chung Wu; Yung-Che Tseng; Ming-Yi Chou; Pung-Pung Hwang (Journal of Hazardous Materials, 2024)

Efficient PDS activation and carrier extraction by Gd2O3 decorated SrTiO3 for Fenton-like photocatalysis - Bo Feng; Kaining Sun; Guangbo Che; Tianyi Yang; Yongya Zhang; Qianqian He; Tianrui Chang; Lijing Wang; Renquan Guan (Chemical Engineering Journal, 2024)

In enzymatic reactions, the reverse reaction reduces product noise - Ching-Chu Hsieh; Yung-Chun Lin; Wei-Bo Lin; Che-Chi Shu (BioSystems, 2024)

Analysis of the spatiotemporal changes in global tropospheric ozone concentrations from 1980 to 2020 - Bo Liang; Jianjun He; Lifeng Guo; Yarong Li; Lei Zhang; Huizheng Che; Sunling Gong; Xiaoye Zhang (Science of The Total Environment, 2024)

Complete genome sequence analysis and Pks genes identification of Brevibacillus brevis FJAT-0809-GLX with a broad inhibitory spectrum against phytopathogens - Jianmei Che; Chengchun Lai; Gongti Lai; Bingxing Chen; Liyuan He; Bo Liu (World Journal of Microbiology and Biotechnology, 2024)

Fabrication of carbon-coated iron-based porous heterogeneous Fenton catalyst and enhanced degradation performance towards ciprofloxacin - Yufan Mo; Chunxia Che; Wei Han; Feiran Chen; Jun Guan; Feng Zhang; Bo Yang; Xiangdong Ren; Huiyu Li; Saeed Ahmed; Yongjun Feng (Chemical Engineering Journal, 2024)

Highly-separated Co anchored on S, O-doped carbon nitride for enhanced peroxymonosulfate activation: Insights into radical and non-radical pathways - Yuhang Deng; Simiao Wang; Tianyu Zhou; Bo Liu; Bo Hu; Liang Wang; Chunbo Liu; Wei Jiang; Guangbo Che (Chemical Engineering Journal, 2024)

A review on ‘source prevention, process control, end recovery’ trinity-comprehensive treatment technology for acid mine drainage - Yu Yang; Bo Li; Lulu Che; Menghua Li; Pu Liu; Tao Li; Ye Luo (Process Safety and Environmental Protection, 2024)

Self-reconstructed ZIF-L/Co(OH)2 heterointerface modulates electronic structure of Ru and boosts electrocatalytic hydrogen evolution - Xinhui Yu; Yi Chen; Yuanyuan Wu; Xianyu Chu; Bo Liu; Bo Hu; Guangbo Che; Wei Jiang; Chunbo Liu (Chemical Engineering Journal, 2024)

Climate factors influencing springtime dust activities over Northern East Asia in 2021 and 2023 - Lin Liu; Zhili Wang; Huizheng Che; Deying Wang; Ke Gui; Bo Liu; Kangjie Ma; Xiaoye Zhang (Atmospheric Research, 2024)

Characterization of lamb shashliks with different roasting methods by intelligent sensory technologies and GC–MS to simulate human muti-sensation: Based on multimodal deep learning - Che Shen; Guanhua Cai; Jiaqi Tian; Xinnan Wu; Meiqi Ding; Bo Wang; Dengyong Liu (Food Chemistry, 2024)

Spatiotemporal comprehensive evaluation of water quality based on enhanced variable fuzzy set theory: A case study of a landfill in karst area - Yu Yang; Bo Li; Chaoyi Li; Pu Liu; Tao Li; Ye Luo; Lei Yang; Lulu Che; Menghua Li (Journal of Cleaner Production, 2024)

The ability of energy commodities to hedge the dynamic risk of epidemic black swans - I-Chun Tsai; Han-Bo Chen; Che-Chun Lin (Resources Policy, 2024)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

A review of treatment technologies for acid mine drainage and sustainability assessment - Yu Yang; Bo Li; Tao Li; Pu Liu; Beibei Zhang; Lulu Che (Journal of Water Process Engineering, 2023)

Characterization of selected commercially available grilled lamb shashliks based on flavor profiles using GC-MS, GC × GC-TOF-MS, GC-IMS, E-nose and E-tongue combined with chemometrics - Che Shen; Yun Cai; Xinnan Wu; Shengmei Gai; Bo Wang; Dengyong Liu (Food Chemistry, 2023)

Investigation on the adsorption characteristics of pharmaceuticals and personal care products on polyethylenimine-alginate-activated carbon composite fiber - Se-Been Mun; Minhee Han; Yub Raj Dangi; Bo-Gyeon Cho; Se-Ra Jin; Kwan-Yong Lee; Che-Ryong Lim; Chul-Woong Cho; Yeoung-Sang Yun (Desalination, 2023)

Typhoon-related changes in moisture pathways and sources for precipitation in Eastern China during the three major rainy seasons - Jinning Che; Bo Liu; Lei Chen; Guoyu Ren; Tianjun Zhou (Atmospheric Research, 2023)

A Simplified Analytical Elastoplastic Embedment Depth Model of Proppant Based on the Drucker–Prager Yield Criterion - Bo He; Lingzhi Xie; Yongxin Che; Yao Zhang; Jun Liu (Rock Mechanics and Rock Engineering, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

Tracing the future of epidemics: Coincident niche distribution of host animals and disease incidence revealed climate‐correlated risk shifts of main zoonotic diseases in China - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Yiyang Su; Lingyu Che; Meng Zhang; Yumeng Lu; Pufan Gao; Jingjing Yang; Ying Xue; Guishuang Li (Global Change Biology, 2023)
Climate has critical roles in the origin, pathogenesis and transmission of infectious zoonotic diseases. However, large‐scale epidemiologic trend and specific response pattern of zoonotic diseases under future climate scenarios are poorly understood. Here, we projected the distribution shifts of transmission risks of main zoonotic diseases under climate change in China. First, we shaped the global habitat distribution of main host animals for three representative zoonotic diseases (2, 6, and 12 hosts for dengue, hemorrhagic fever, and plague, respectively) with 253,049 occurrence records using maximum entropy (Maxent) modeling. Meanwhile, we predicted the risk distribution of the above three diseases with 197,098 disease incidence records from 2004 to 2017 in China using an integrated Maxent modeling approach. The comparative analysis showed that there exist highly coincident niche distributions between habitat distribution of hosts and risk distribution of diseases, indicating that the integrated Maxent modeling is accurate and effective for predicting the potential risk of zoonotic diseases. On this basis, we further projected the current and future transmission risks of 11 main zoonotic diseases under four representative concentration pathways (RCPs) (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) in 2050 and 2070 in China using the above integrated Maxent modeling with 1,001,416 disease incidence records. We found that Central China, Southeast China, and South China are concentrated regions with high transmission risks for main zoonotic diseases. More specifically, zoonotic diseases had diverse shift patterns of transmission risks including increase, decrease, and unstable. Further correlation analysis indicated that these patterns of shifts were highly correlated with global warming and precipitation increase. Our results revealed how specific zoonotic diseases respond in a changing climate, thereby calling for effective administration and prevention strategies. Furthermore, these results will shed light on guiding future epidemiologic prediction of emerging infectious diseases under global climate change.

Study on the reinforcement mechanism of grouted bolts with or without prestress via the hybrid DEM-FDM method - Mingjing Jiang; Yingjun Bo; Huaning Wang; Na Che (Transportation Geotechnics, 2023)

Adsorption of organic micropollutants on yeast: Batch experiment and modeling - Se-Been Mun; Bo-Gyeon Cho; Se-Ra Jin; Che-Ryong Lim; Yeoung-Sang Yun; Chul-Woong Cho (Journal of Environmental Management, 2023)

Consumer culture in traditional food market: The influence of Chinese consumers to the cultural construction of Chinese barbecue - Bo Wang; Che Shen; Yun Cai; Limei Dai; Shengmei Gai; Dengyong Liu (Food Control, 2023)

Effects of Toxin-Antitoxin System HicAB on Biofilm Formation by Extraintestinal Pathogenic E. coli - Bo Hou; Chen-Yan Wang; Shao-Wen Li; Lun-Jiang Zhou; Yong-Liang Che; Qiu-Yong Chen (Current Microbiology, 2023)

Succession of Bacterial Community Function in a Continuous Composting System with Spent Mushroom Substrate and Sawdust as Bulking Agents - Qianqian Chen; Bo Liu; Jianmei Che; Guohong Liu; Huai Shi; Jieping Wang; Lulong Zhong (Journal of Soil Science and Plant Nutrition, 2022)

ceRNA network of lncRNA MIR210HG/miR-377-3p/LMX1A in malignant proliferation of glioma cells - Zhikuan Yu; Ningwei Che; Yeting He; Bo Zhang (Genes & Genomics, 2022)

Evansella halocellulosilytica sp. nov., an alkali-halotolerant and cellulose-dissolving bacterium isolated from bauxite residue - Guo-Hong Liu; Manik Prabhu Narsing Rao; Qian-Qian Chen; Jian-Mei Che; Huai Shi; Bo Liu; Wen-Jun Li (Extremophiles, 2022)

Characterization and Anticancer Activity of a Folic Acid Conjugated and Cationic Peptide L-K6 Encapsulated Cancer-Targeting Liposomal Drug Delivery System - Ying Wang; Huan Xu; Bo Wang; Ruixue Wang; Che Wang; Dejing Shang (International Journal of Peptide Research and Therapeutics, 2022)

Neobacillus rhizophilus sp. nov. and Neobacillus citreus sp. nov., isolated from the citrus rhizosphere soil - Guo-Hong Liu; Manik Prabhu Narsing Rao; Qian-Qian Chen; Huai Shi; Jian-Mei Che; Bo Liu; Wen-Jun Li (Archives of Microbiology, 2022)

Correction to: Lederbergia citri sp. nov., and Lederbergia citrisecundus sp. nov., isolated from citrus rhizosphere - Guo‑Hong Liu; Manik Prabhu Narsing Rao; Qian‑Qian Chen; Jian‑Mei Che; Huai Shi; Bo Liu; Wen‑Jun Li (Current Microbiology, 2022)

On-Site Investigations of Coastal Erosion and Accretion for the Northeast of Taiwan - Ting-Yu Liang; Chih-Hsin Chang; Shih-Chun Hsiao; Wei-Po Huang; Tzu-Yin Chang; Wen-Dar Guo; Che-Hsin Liu; Jui-Yi Ho; Wei-Bo Chen (Journal of Marine Science and Engineering, 2022)
Coastal erosion is a major natural hazard along the northeastern shoreline (i.e., Yilan County) of Taiwan. Analyses of the evolution of the 0 m isobath of the Yilan County coastline indicate that erosion and accretion are occurring north and south of Wushi Fishery Port, respectively, because of jetty and groin construction. Topographic and bathymetric surveys involving the measurement of 43 cross sections were conducted in 2006, 2012, 2013, and 2019. The cross-shore profile comparisons reveal that the erosion of onshore dunes is significant in the northern Jhuan River estuary. Due to the establishment of a nature reserve in the southern Lanyang River estuary, the sediments are carried northward by tidal currents, and accretion is inevitable in the northern Lanyang River estuary. The results of the bathymetric surveys also suggest that the shoreline of Yilan County tends to accrete in summer because of abundant sediment from the rivers; however, it is eroded in winter, owing to the large waves induced by the northeast monsoon. Additionally, the calculated net volume of erosion and accretion between each pair of cross sections shows that the length of coastline impacted by estuarine sediment transport is approximately 2 km long from north to south along the coastline of the Lanyang River estuary.

Notch activation suppresses endothelial cell migration and sprouting via miR-223-3p targeting Fbxw7 - Ruonan Wang; Ziyan Yang; Liang Liang; Xingxing Feng; Bo Che; Xiaoyan Zhang; Qijun Zheng; Xianchun Yan; Hua Han (In Vitro Cellular & Developmental Biology - Animal, 2022)

Lederbergia citri sp. nov., and Lederbergia citrisecundus sp. nov., isolated from citrus rhizosphere - Guo-Hong Liu; Manik Prabhu Narsing Rao; Qian-Qian Chen; Jian-Mei Che; Huai Shi; Bo Liu; Wen-Jun Li (Current Microbiology, 2022)

Critical Risk Indicators (CRIs) for the electric power grid: a survey and discussion of interconnected effects - Judy P. Che-Castaldo; Rémi Cousin; Stefani Daryanto; Grace Deng; Mei-Ling E. Feng; Rajesh K. Gupta; Dezhi Hong; Ryan M. McGranaghan; Olukunle O. Owolabi; Tianyi Qu; Wei Ren; Toryn L. J. Schafer; et al. (Environment Systems and Decisions, 2021)

Development of a region-partitioning method for debris flow susceptibility mapping - Shuang-shuang Qiao; Sheng-wu Qin; Jing-bo Sun; Wen-chao Che; Jing-yu Yao; Gang Su; Yang Chen; Uzodigwe Emmanuel Nnanwuba (Journal of Mountain Science, 2021)

Single-nucleotide polymorphisms responsible for pseudo-albinism and hypermelanosis in Japanese flounder (Paralichthys olivaceus) and reveal two genes related to malpigmentation - Bo Zhang; Kangkang Peng; Jinyuan Che; Na Zhao; Lei Jia; Dongkang Zhao; YaJuan Huang; YongGuan Liao; Xiaoxu He; Xiaoling Gong; Baolong Bao (Fish Physiology and Biochemistry, 2021)

Neobacillus sedimentimangrovi sp. nov., a Thermophilic Bacterium Isolated from Mangrove Sediment - Rong Tang; Qi Zhang; Manik Prabhu Narsing Rao; Guo-Hong Liu; Jian-Mei Che; Min Lei; Bo Liu; Wen-Jun Li; Shun-Gui Zhou (Current Microbiology, 2021)

Reclassification of Brevibacterium frigoritolerans DSM 8801T as Bacillus frigoritolerans comb. nov. Based on Genome Analysis - Guo-Hong Liu; Bo Liu; Jie-Ping Wang; Jian-Mei Che; Peng-Fei Li (Current Microbiology, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Genome-based reclassification of Bacillus plakortidis Borchert et al. 2007 and Bacillus lehensis Ghosh et al. 2007 as a later heterotypic synonym of Bacillus oshimensis Yumoto et al. 2005; Bacillus rhizosphaerae Madhaiyan et al. 2011 as a later heterotypic synonym of Bacillus clausii Nielsen et al. 1995 - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Jian-Mei Che; Qian-Qian Chen; Cetin Sengonca; Bo Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Seminal Plasma Exosomes: Promising Biomarkers for Identification of Male and Pseudo-Males in Cynoglossus semilaevis - Bo Zhang; Na Zhao; Lei Jia; Kang Peng; Jinyuan Che; Kunming Li; Xiaoxu He; Jinsheng Sun; Baolong Bao (Marine Biotechnology, 2019)

Spatio-temporal evolution and the influencing factors of PM2.5 in China between 2000 and 2015 - Liang Zhou; Chenghu Zhou; Fan Yang; Lei Che; Bo Wang; Dongqi Sun (Journal of Geographical Sciences, 2019)

Interferon-γ regulates cell malignant growth via the c-Abl/HDAC2 signaling pathway in mammary epithelial cells - Wen-bo Ren; Xiao-jing Xia; Jing Huang; Wen-fei Guo; Yan-yi Che; Ting-hao Huang; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

A corn straw-based diet increases release of inflammatory cytokines in peripheral blood mononuclear cells of dairy cows - Yan-yi Che; Xiao-jing Xia; Bo-ping He; Yuan-yuan Gao; Wen-bo Ren; Hong-tao Liu; Jian-fang Liu; Ting-hao Huang; Wen-yu Han; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2018)

Effects of Brevibacillus brevis FJAT-1501-BPA on growth performance, faecal microflora, faecal enzyme activities and blood parameters of weaned piglets - Jianmei Che; Shaowen Ye; Bo Liu; Yuanyuan Deng; Qianqian Chen; Cibin Ge; Guohong Liu; Jieping Wang (Antonie van Leeuwenhoek, 2016)

Modeling the interaction between tides and storm surges for the Taiwan coast - Wen-Cheng Liu; Wei-Che Huang; Wei-Bo Chen (Environmental Fluid Mechanics, 2016)

Functional analysis of β-amyrin synthase gene in ginsenoside biosynthesis by RNA interference - Che Zhao; Tianhui Xu; Yanlong Liang; Shoujing Zhao; Luquan Ren; Qian Wang; Bo Dou (Plant Cell Reports, 2015)

Development of a test strip for rapid detection of lactoperoxidase in raw milk - Hong-xia Che; Bo Tian; Li-na Bai; Li-ming Cheng; Li-li Liu; Xiao-na Zhang; Zhan-mei Jiang; Xiao-xi Xu (Journal of Zhejiang University-SCIENCE B, 2015)

Down-regulation of eIF5A-2 prevents epithelial-mesenchymal transition in non-small-cell lung cancer cells - Guo-dong Xu; Xin-bao Shi; Le-bo Sun; Qing-yun Zhou; Da-wei Zheng; Huo-shun Shi; Yong-liang Che; Zi-shan Wang; Guo-feng Shao (Journal of Zhejiang University-SCIENCE B, 2013)

Statin use and risk of bladder cancer: a meta-analysis - Xiao-long Zhang; Jiang Geng; Xiao-peng Zhang; Bo Peng; Jian-ping Che; Yang Yan; Guang-chun Wang; Sheng-qiang Xia; Yan Wu; Jun-hua Zheng (Cancer Causes & Control, 2013)

Combination of flavopiridol and embelin effectively inhibit cell growth in hepatocellular carcinoma depending on regulatory relationship between CDK6 and XIAP - Yufang Che; David Y. Zhang; Fei Ye; Benyan Wu; Bo Jiang (Medicinal Chemistry Research, 2012)

Double-antigen sandwich ELISA for detection of antibodies to SARS-associated coronavirus in human serum - S. Chen; D. Lu; M. Zhang; J. Che; Z. Yin; S. Zhang; W. Zhang; X. Bo; Y. Ding; S. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2005)